Combustion Characteristics of Ethanol with Ignition Improver in a Small Diesel Engine during Start-up - Iempremjit, Kitti (Princess of Naradhiwas University Journal, 2021)
This work aimed to study the combustion characteristics of ethanol with ignition improver, glycerol ethoxylate (GE) during start-up condition. Preliminary test performed in a diesel engine with a compression ratio of 18 and varying concentrations of GE from 2-35%. Results showed the ethanol blended with ignition improver concentration from 2-35% unable to start the engine. The modified diesel engine with a compression ratio of 23 was tested under controlled room conditions with varying concentrations of GE. The results showed the ethanol blended with minimum ignition improver concentration for starting the engine was 13%. Effects of improver concentration on combustion characteristics during start-up conditions were analyzed by measuring the in-cylinder pressure. Results showed that there were fewer variations of the start of injection (SOI) and start of combustion (SOC) when the concentration of ignition improvers more than 24%. The differences with diese were 2.5-3%, 3.0-3.8° and 3.4-8.8° for IMEP, SOI and SOC, respectively. The increased concentrations of ignition improvers reduced ignition delay (ID) and the number of misfire cycles in the engine during start-up period. Ethanol with 28% GE was the minimal amounts of ignition improver required to meet almost zero misfire cycles as in the diesel case.